2015
DOI: 10.1371/journal.pone.0129937
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lipid Levels Influence Lipid Deposition in the Liver of Large Yellow Croaker (Larimichthys crocea) by Regulating Lipoprotein Receptors, Fatty Acid Uptake and Triacylglycerol Synthesis and Catabolism at the Transcriptional Level

Abstract: Ectopic lipid accumulation has been observed in fish fed a high-lipid diet. However, no information is available on the mechanism by which dietary lipid levels comprehensively regulate lipid transport, uptake, synthesis and catabolism in fish. Therefore, the present study aimed to gain further insight into how dietary lipids affect lipid deposition in the liver of large yellow croaker(Larimichthys crocea). Fish (150.00±4.95 g) were fed a diet with a low (6%), moderate (12%, the control diet) or high (18%) crud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
107
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 70 publications
18
107
0
Order By: Relevance
“…This result may reveal that reduced dgat-2 gene expression could partially be due to a feedback mechanism involving excessive lipid accumulation in the liver, which has been observed in a mouse model of high-fat diet-induced obesity [79]. Many studies have shown that dietary fatty acid composition and lipid levels can affect lipogenesis and lipolysis [37]. The inconformity between lipid related-metabolism enzyme activities and gene expression levels should be deeply explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result may reveal that reduced dgat-2 gene expression could partially be due to a feedback mechanism involving excessive lipid accumulation in the liver, which has been observed in a mouse model of high-fat diet-induced obesity [79]. Many studies have shown that dietary fatty acid composition and lipid levels can affect lipogenesis and lipolysis [37]. The inconformity between lipid related-metabolism enzyme activities and gene expression levels should be deeply explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely cultured in south-eastern China coastal areas, especially in Fujian and Zhejiang Provinces [33]. Studies on the lipid nutrition of this fish have been conducted intensively in the past few years [4, 3437]. Yi et al [38] reported that there was no significant effect of dietary FO replacement by rapeseed oil on growth and body composition, although the fatty acid compositions of muscle and skin color were significantly influenced by dietary lipid sources.…”
Section: Introductionmentioning
confidence: 99%
“…The survival rate (81.5–93.9%), final mean weight (269.3–281.6 g) and specific growth rate (0.77–0.85% per day) of the fish were not significantly affected by dietary lipid levels ( P > 0.05) (Yan et al . ). Compared with the control group, muscle lipid content was significantly lower in the low‐lipid group, whereas it was significantly higher in the high‐lipid group (Table ; P < 0.05).…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, we previously showed that dietary lipid levels regulated the expression of ldlr , lrp1 , cd36 , fatp1 , fabp11 and fabp3 in the liver of large yellow croaker (Yan et al . ). Collectively, these data strongly support the hypothesis that lipid metabolism in muscle and adipose tissue may also be influenced at the transcriptional level by dietary lipid levels in fish.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation